Serum IL-40 is elevated in systemic sclerosis and is linked to disease activity, gastrointestinal involvement, immune regulation and fibrotic processes - Adéla Navrátilová; Sabína Oreská; Hana Wünsch; Klára Mocová; Ondřej Kodet; Marian Rybar; Glenda Alquicer; Aneta Prokopcová; Viktor Bečvář; Radim Bečvář; Aneta Jiránková; Anna Bobrová; et al. (Arthritis Research & Therapy)
Abstract Background Interleukin 40 (IL-40) is a cytokine implicated in malignancies and rheumatic disorders. Its association with fibrotic mediators has been previously described. Since inflammation and fibrosis are hallmarks of systemic sclerosis (SSc), we aimed to analyze the role of IL-40 in SSc. Methods IL-40 levels were analyzed in the serum of 90 SSc patients and 75 healthy controls (HCs). IL-40 expression in dermal biopsies from 5 SSc patients and 5 HCs was assessed via immunohistochemistry. IL-40 was analyzed in 39 SSc patients with interstitial lung disease treated with cyclophosphamide (CPA) and in 24 SSc patients with active progressive disease treated with rituximab (RTX). SSc activity was assessed by the European Scleroderma Study Group (ESSG) index. The effect of recombinant IL-40 on peripheral blood mononuclear cells (PBMCs) from 10 SSc patients was determined in vitro. IL-40 was analyzed in 24 individuals at risk of developing SSc (VEDOSS), who were categorized as progressors (n = 11) and nonprogressors (n = 13). Results IL-40 expression was elevated in the skin of SSc patients compared to HCs, particularly in fibroblasts and immune infiltrates. Serum IL-40 was increased in SSc compared to HCs (p < 0.0001) and was associated with ESSG (r = 0.372, p = 0.0005) and gastrointestinal involvement (p < 0.05). IL-40 correlated with serum IL-8 (r = 0.270, p = 0.019) and TGF-β1 (r = 0.301, p = 0.024) levels. In the CPA and RTX cohort, no significant changes in the serum IL-40 were observed upon treatment. Baseline and changes in IL-40 levels were associated with changes in several clinical parameters. IL-40 was elevated in patients at risk of SSc compared to HCs (p = 0.0003). No significant changes were observed in progressors vs. nonprogressors; however, IL-40 was associated with capillaroscopy findings (p < 0.05). IL-40 induced the upregulation of IL-6 (p = 0.002), MCP-1 (p = 0.002) and IL-10 (p = 0.002) in PBMCs from SSc patients in vitro. Conclusions IL-40 was upregulated in the skin and serum of SSc patients and was associated with disease activity, gastrointestinal involvement and fibrotic mediators. Our in vitro findings indicate that IL-40 might be involved in the immune response and fibrotic processes in SSc.